(±)-Pheharmines A–B, two pairs of racemic alkaloids with a morpholino[4, 3, 2-hi]β-carboline core, from the roots of Peganum harmala. Issue 43 (24th October 2022) - Li, Sheng-Ge; Hu, Xu; Zhang, Qin; Zan, Yan-Hui; Wang, Kai-Bo; Jiang, Chun-Yu; Xue, Jing-Jing; Liu, Yong-Xiang; Lin, Bin; Jing, Yong-Kui; Li, Da-Hong; Hua, Hui-Ming
Abstract : Two pairs of unprecedented β-carboline-phenylpropanoid alkaloids, (±)-pheharmines A–B (1–4 ), characterized by a morpholino[4, 3, 2- hi ]β-carboline core with two chiral centers, were isolated from the roots of Peganum harmala . Abstract : Two pairs of unprecedented β-carboline-phenylpropanoid heterogeneous alkaloids, (±)-pheharmines A–B (1–4 ), characterized by a morpholino[4, 3, 2- hi ]β-carboline core with two chiral centers, were isolated from the roots of Peganum harmala . The structures, including their absolute configurations, were identified using spectroscopic analyses and electronic circular dichroism (ECD) calculations. The biosynthetic hypothesis for the formation of pheharmines A–B was proposed. Compounds 1–4 exhibited moderate cytotoxic activities against HL-60 cell lines.